The Effects of Selected Macroeconomic Variables on Tourism Demand for the South Moravian Region of the Czech Republic from Germany, Poland, Austria, and Slovakia - Tomaś Jerab́ek (Comparative Economic Research. Central and Eastern Europe, 2019)
International tourism is one of the most important sectors of the open economy. The aim of this paper is to investigate the effects that income as gross domestic product, tourism price as the real exchange rate, and travel cost as the price of Brent crude oil have on inbound tourism demand (tourist arrivals) from Poland, Slovakia, Germany, and Austria in the South Moravian Region of the Czech Republic over the period 2002:M1-2018:M5. The number of Polish, German, Slovak and Austrian tourists accommodated in collective accommodation establishments within the South Moravian Region as a dependent variable are considered. To achieve this aim, cointegration analysis under the VECM approach is applied. The results show that Slovak, Polish, Austrian and German tourists respond positively to their income changes. Austrian and Slovak tourists respond negatively to changes in tourism prices in the Czech Republic. Tourists from Germany and Poland do not respond to changes in the Czech price level since their elasticity coefficients are non-significant. German, Austrian and Slovak tourists respond negatively to transportation cost changes. Polish tourists do not respond to transport cost changes since their elasticity coefficient is non-significant.
Keywords: F14; F47; Z03; 330; tourism demand; real exchange rate; industrial production index; crude oil price; VECM; cointegration